Avaliação eletrofisiológica da ação dos antioxidantes glutation e ácido alfalipóico em um modelo animal de isquemia cerebral - Vale, Otoni Cardoso do (2000)
An animal model for brain ischemia was developed. An electroencephalographic analysis of several band fi'equency absolute amplitudes has been performed m order to demonstrate the effects on cerebral electric activity induced by ischemia, followmg common carotid arteries büateral obüteration in Wistar-Kyoto rats, anaesthetized with urethane. The waves were recorded fi-om subcutaneous electi-odes on left frontal (F3), right frontal (F4), left parietal (P3), right parietal (P4) and vertex (Cz) regions. This electi-ophysiological analysis consisted of the absolute amplitude means evaluation of the several frequency spectra (alpha, betai, betaz, betas, theta and delta). The cerebral electrical activity was picked up by an appropriate hardware and a software system for analysis. It has been verified a highly significant reduction of the absolute amplitude means of the spectrum waves (P<0,015) after both common carotid arteries occlusion. The miusion of 1.2 mM reduced glutathione solution into the cephalic segment of the left common carotid artery of Wistar-Kyoto rats significantly reverted the depression of the absolute amplitudes of the several spectral frequencies of the electroencephalogram (P<0,05) induced by obüteration of both common carotid arteries. The infusion of 0,12 mM reduced glutafhione or saline solution into the cephalic segment of the left common carotid artery of the same animals did not reverted significantly the depression oftiie electroencephalographic wave absolute amplitudes mduced by obuteration of both common carotid arteries. The occlusion of left common carotid artery in urethane anaesthetized Wistar-Kyoto rats caused less significant absolute amplitude reduction than both carotid arteries occlusion and the the absolute amplitude recovery with intracarotid 1,2 mM reduced glutathione infusion was less evident. The left intracarotid infusion of 0,12 mM reduced glutathione m rats with bilateral common 281 carotid arteries occlusion reverted the ischemic absolute amplitude reduction of only right frontal betai hypersynchronic activity (P<0,05), but induced NREM sleep electi'ophysiological activity (P<0,05). The intracarotid infusion of 2,1 mM L-cystine or 1,2 mM L-glutanüne in rats wiüi both common carotid arteries occlusion did not cause consistent absolute amplitude modifications of the electoencephalographic spectral waves. The inti'acarotid infusion of 3,03 mM a-1ipoic acid in rats with both common carotid arteries occlusion caused initial reduction and partial final absolute amplitude recuperation of several specti-al band fi-equencies (P<0,05); the mtracarotid infusion of 6,06 mM a-1ipoic acid significantly reverted the ischemic depression of the absolute amplitudes of frontal theta and right parietal delta spectra; the mtracarotid infusion of 60,6 mM a-1ipoic acid significantly increased Uie absolute amplitude ischemic-mduced depression of ahnost all specti-al electroencephalographic waves (P<0,05). Fmally, It has been demonstrated that intracarotid 1,2 mM reduced glutathione and 6,06 mM a-1ipoic acid m rats with both common carotid arteries occlusion increased the inu-acerebral level of reduced glutathione (P<0,05). It was concluded that an appropriated electroencephalographic analysis of Wistar-Kyoto rats with both carotid arteries occlusion is a valuable study model of cytotoxic effects of cerebral ischemia and could be used to verify fhe cytoprotector reduced glutathione effect and both pro-oxidant and oxidant a-1ipoic acid action, as weU as other drug effect studies